1984
DOI: 10.1159/000123946
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adrenergic and Cholinergic Antagonists on Central Histaminergic Stimulation of Pituitary-Adrenocortical Response under Stress in Rats

Abstract: A possible interaction of central histaminergic receptors with adrenergic and cholinergic muscarinic neurons in increasing the pituitary-adrenocortical response under stress, assessed indirectly from the corticosterone concentration in blood serum, was investigated in conscious rats. All the drugs were administered intracerebroventriculary, the antagonists 15 to 30 min prior to the agonists. The histamine-induced increase in serum corticosterone levels of stressed rats was considerably antagonized by prazosin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…All compounds were dissolved in saline except Pra, which was dissolved in saline acidified with 0.1  N HCl and adjusted with 0.1  N NaOH to pH 7.4. The dose of 1 mmol used is approximately similar to the doses of adrenergic receptor antagonists previously found to affect stimulated ACTH and PRL secretion [25, 27, 28, 37, 38]. …”
Section: Methodsmentioning
confidence: 94%
“…All compounds were dissolved in saline except Pra, which was dissolved in saline acidified with 0.1  N HCl and adjusted with 0.1  N NaOH to pH 7.4. The dose of 1 mmol used is approximately similar to the doses of adrenergic receptor antagonists previously found to affect stimulated ACTH and PRL secretion [25, 27, 28, 37, 38]. …”
Section: Methodsmentioning
confidence: 94%
“…However, neither antagonist was effective in inhibiting the histamineinduced increase in plasma ACTH and corticosterone concentrations. On the contrary, Bugajski & Gadek (1983) reported that cimetidine and metiamide inhibited histamineinduced corticosterone increase. It seems likely that histamine-induced hormone secretion is mediated mainly through HI-receptor, and to a lesser extent through the H2-receptor.…”
Section: Discussionmentioning
confidence: 93%
“…histamine injection. On the other hand, Bugajski & Gadek (1983) demonstrated that in stressed rats, the corticosterone response to histamine is mediated by both H,-and H2-central receptors. Also, it has been reported that the H2-receptor is responsible for histamine-induced ACTH release in rats and man (Morita & Koyama, 1979;Knigge et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…There is a high density of brain mast cells in regions situated at the boundary between the central nervous system (CNS) and its surroundings [such as in the circumventricular organs (8,17) and median eminence (38,41,42,53)]. Administration of histamine into the cerebral third ventricle (V III ) leads to increases in various stress hormones [such as ACTH-adrenocortical hormones (6,42,57,66) and catecholamines (16)] in the peripheral circulation. Histamine and its receptors are highly concentrated within the hypothalamus (4,6,40,57,59), and various types of stress induce significant alterations in both histamine synthesis and its concentration in several brain regions (5,57,59,63).…”
mentioning
confidence: 99%
“…Administration of histamine into the cerebral third ventricle (V III ) leads to increases in various stress hormones [such as ACTH-adrenocortical hormones (6,42,57,66) and catecholamines (16)] in the peripheral circulation. Histamine and its receptors are highly concentrated within the hypothalamus (4,6,40,57,59), and various types of stress induce significant alterations in both histamine synthesis and its concentration in several brain regions (5,57,59,63). Renin secretion is activated via the hypothalamic-sympathetic outflow during various forms of stress (1,14,60) and also during cardiovascular dysfunction (3,13,26,33,35,36,58).…”
mentioning
confidence: 99%